Design and implementation of user-customizing oriented multipath inter-domain routing system - Dong-hong QIN; Jia-hai YANG; Yang YANG; Hui ZHANG (Tongxin xuebao)
With the rapid growth of Internet applications,the routing flexibility and quality of the inter-domain routing system face some significant challenges.Multipath routing is an important method of improving the reliability and robustness of the Internet.Based on previous researches,orienting user customizing routing service,a multi-path inter-domain routing system named UMIR was developed.The routing system includes three service functions of controlling and management center,route discovery and computing protocol and routing incentive,and it is made of control and management subsystem,routing protocol subsystem and routing incentive subsystems.Based on the Emulab network test platform of University of Utah,the UMIR routing system was deployed and tested.The experimental results show that the routing system is running correctly to achieve our design goals.